Impact of building walls of historic objects from half-timbered wall in their state of thermal protection = Wpływ budowy ścian historycznych budynków z muru pruskiego na ich stan ochrony cieplnej - Szymanowska-Gwiżdż, Agnieszka; Steidl, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the problems connected with preserved examples of buildings in Upper Silesia that contain the elements of half-timbered walls. This type of construction currently characterizes houses of various utility functions. Often, their formation was related to the construction of patron settlements, accompanied by the development of industrial plants.
Keywords: mur pruski; izolacyjność termiczna; ochrona cieplna; half-timbered wall; thermal insularity; thermal protection